2004
DOI: 10.1111/j.1600-0501.2004.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical aspects of marginal bone resorption around osseointegrated implants: considerations based on a three‐dimensional finite element analysis

Abstract: The results of this analysis suggest that a certain amount of conical resorption may be the result of biomechanical adaptation of bone to stress. However, as bone resorption progresses, the increasing stresses in the cancellous bone and implant under lateral load may result in implant failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(153 citation statements)
references
References 46 publications
9
133
1
10
Order By: Relevance
“…Increased strain at the distal side of the implant loading side has been reported in several in vitro studies using parallel (30,37,39) and inclined (40) implants. Furthermore, the increased strain observed on the lingual surface of the vertically oriented implant at the nonloading side in this study is consistent with another investigation (41), in which the authors reported increased lingual stresses near the implant neck. The upper edges of the cortical bone demonstrated a tendency to be displaced inward within the horizontal plane.…”
Section: Discussionsupporting
confidence: 82%
“…Increased strain at the distal side of the implant loading side has been reported in several in vitro studies using parallel (30,37,39) and inclined (40) implants. Furthermore, the increased strain observed on the lingual surface of the vertically oriented implant at the nonloading side in this study is consistent with another investigation (41), in which the authors reported increased lingual stresses near the implant neck. The upper edges of the cortical bone demonstrated a tendency to be displaced inward within the horizontal plane.…”
Section: Discussionsupporting
confidence: 82%
“…When pathological overloading occurs (over 4,000 microstrain), strain gradients exceed the physiological limits of the bone, which may cause micro-fractures at the bone-implant interface, and bone resorption 47) . The increased strain at lingual and buccal surfaces on the loading side during first premolar loading concurred with another investigation 48) in which the authors reported that the upper edges of the cortical bone plate had the potential tendency to be displaced inward and outward in the horizontal plane. They added that the presence of the rigid implant hindered these displacements and led to the occurrence of compressive and tensile stresses on the lingual and buccal sides of upper edges respectively.…”
Section: Discussionsupporting
confidence: 74%
“…The biomechanical aspects are important in the evaluation of the risk of bone resorption that affects the stability efficiency of the prosthesis over time (1). After implant insertion and its subsequent initial loading, crestal bone undergoes remodelling and resorption (2).…”
Section: Introductionmentioning
confidence: 99%